Nutritional demand of 'Grande Naine' and 'Prata Comum' banana bunches in two growing seasons - de Oliveira, Cibelle Tamiris; Rozane, Danilo Eduardo [UNESP]; Pavarin, Levi Godke Faber [UNESP]; Akamine, Henrique Shiniyti [UNESP]; da Silva, Silvia Helena Modenese Gorla [UNESP]; Lima, Juliana Domingues [UNESP] (FapUNIFESP (SciELO), 2022)
The quantification of nutrients accumulated and exported by banana bunches provides information on the crop nutritional requirements. Thus, the aim of this work was to determine the nutritional demand of 'Grande Naine' and 'Prata Comum' banana bunches in the region of Vale do Ribeira, state of São Paulo. Bunch sampling was carried out in six harvest seasons, summer, and winter. The results of dry matter production and nutrient accumulation in bunches were submitted to analysis of variance. Relative growth rates (TCR), organogenic net accumulation (TALON), export and order of nutrient accumulation in bunches were estimated. K and N were the nutrients most accumulated and exported by both cultivars. In harvest period 5 (commercial harvest), more dry matter was produced in the summer and more nutrients were accumulated in the winter. The highest TCR values were observed between periods 2 and 3 in the summer and between 0 and 1 in the winter, but it did not always follow TALON. The results obtained are important to adapt the nutritional management of these cultivars to the study region, especially in relation to the growing season, due to the longer permanence of the bunch on the plant in the winter and greater demand for nutrients until commercial harvest.
Demanda nutricional de cachos de bananeiras ‘Grande Naine’ e ‘Prata Comum’, em duas épocas de cultivo
Keywords: Musa spp; nutrient accumulation; nutrient export